(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article explores patriotism as both a personal virtue and a concept with legal significance. It discusses how patriotism manifests in individual behavior, including loyalty, love, and devotion to one’s country, as well as responsibility for its welfare. The legal aspect of patriotism is also examined, highlighting citizens’ obligations such as respecting national symbols, upholding laws, and participating in civic duties. The paper emphasizes that patriotism is not only an ethical quality but also a foundation for lawful actions that strengthen the state and society.